What Encourages Physically Inactive People to Start Running? An Analysis of Motivations to Participate in Parkrun and City Trail in Poland - Malchrowicz-Mośko, Ewa; León-Guereño, Patxi; Tapia-Serrano, Miguel Angel; Sánchez-Miguel, Pedro Antonio; Waśkiewicz, Zbigniew (Frontiers in Public Health, 2020)
The aim of this study was to investigate the motivations for beginner runners to take part in Parkrun Poznań and City Trail Poznań, Poland, taking into account their socio-demographical variables. A total of 165 (age: 36.33 ± 10.38) inexperienced runners participated in the diagnostic survey and completed the MOMS (Motivations of Marathoner Scale) questionnaire. The sample consisted of 82 men (49.7%) and 83 women (50.3%). The results showed that men were more likely to start running due to competition-related motivations, while the motivations of women were more often related to affiliation, psychological coping, life meaning, and self-esteem. As age increased, the level of motivation due to personal goal achievement, competition, and recognition scales decreased. The Affiliation Scale was especially important for singles who started running, in comparison with runners who were married or in a relationship. These factors should be taken into consideration by event managers and public health specialists. Promoting safe running among people who have no experience with this sport is as important as encouraging them to run. All runners stated that they would like to run a marathon in the future. Moreover, thanks to initiatives such as City Trail and Parkrun, Polish respondents feel motivated to lead an active lifestyle, with an average score of 4.98 on a 7-point Likert scale.